Primary Phytochemical Analysis of Prangos acaulis (Lindl.) Bornm. and Comparative Analysis with Prangos ferulacea (L.) Lindl - Rashidova, Fatima (НДУ ім. М. Гоголя, 2026)
Prangos is a perennial herb belonging to the Apiaceae family. This genus is primarily distributed in dry and semi-desert climates. Numerous species of the Prangos genus have been studied, and extensive phytochemical analyses have been conducted, revealing that they are rich in biologically active compounds. However, sufficient information regarding Prangos acaulis is lacking. Major classes of phytochemicals with disease- preventive properties include dietary fiber, antioxidants, anticancer agents, detoxifying substances, immune enhancers, and neuropharmacological compounds. The potential richness of the phytochemical composition of this species, considering its pharmacological properties, suggests that it may become a future raw material for medicine, and for this reason, the study of the plant is important. The aim of the research is to perform a phytochemical analysis of P.acaulis and P.ferulacea species using paper chromatography, to conduct preliminary screening for P. acaulis, and to evaluate the obtained results in comparison with P.ferulacea. The percolation method was employed to obtain plant extracts. Both dried and powdered plant samples were accurately weighed to 20 g each. The measured plant material was soaked in 20 ml of 70% ethanol and allowed to stand for 24 hours. After another 24-hour standing period, the liquid was completely filtered and returned to the separating funnel. From the 20 g sample, 80% was collected as the primary extract at a rate of approximately 40 drops per hour and set aside. To conduct the research, the collected plants were dried under identical conditions, ground into powder, extracts were obtained, and the analysis was performed using paper chromatography. Based on the results of the analysis, specific biologically active compounds were identified on the chromatogram, and the Rf values were calculated and compared. The evaluation of the obtained results suggests that the chromatographic profiles of the extracts, in combination with the specific reagents employed, provide insight into the possible functional groups present in the separated compounds. In the present study, a preliminary phytochemical analysis was conducted on 70% ethanol extracts obtained from the leaves and roots of Prangos acaulis using the percolation method. This similarity suggests that P. acaulis may also possess a diverse array of bioactive compounds. Nevertheless, it should be emphasized that further comprehensive and detailed investigations are necessary to accurately identify the specific classes of bioactive substances present and to determine the exact molecular composition of this species.
Keywords: Prangos acaulis, Prangos ferulacea, paper chromatography, phytochemical analysis